Mitigasi Resiko Antara Para Pihak Dan Wanprestasi Dalam Kontrak Pengadaan Barang atau Jasa Pemerintah - Darda Daraba; Sumiyati B; Asdar Arti (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This research aims to analyze risk mitigation between parties in contracts for the procurement of government goods/services and analyze the consequences of default between the parties in contracts for the procurement of government goods/services. The research method used is normative juridical. There are 2 (two) conclusions as a result of the research, first: Mitigation of risks between Parties in Contracts for the procurement of Government Goods/Services. The PPK expects the PPK to pay attention to critical points based on the results of identification in each stage of contract management for the procurement of government goods/services. Second, by mitigating risks, legal certainty and justice can be achieved which provides clarity in carrying out legal actions when implementing contracts in the form of performance even when the contract is in default.